Validating the National Violent Death Reporting System as a Source of Data on Fatal Shootings of Civilians by Law Enforcement Officers. - Conner, Andrew; Azrael, Deborah; Lyons, Vivian H.; Barber, Catherine; Miller, Matthew (American Journal of Public Health, 2019)
Objectives. To evaluate the National Violent Death Reporting System (NVDRS) as a surveillance system for fatal shootings of civilians by law enforcement in the United States. Methods. We cross-linked individual-level mortality data from the 2015 NVDRS and 5 open-source data sets (FatalEncounters.org, Mapping Police Violence, the Guardian 's "The Counted," Gun Violence Archive, and The Washington Post 's "Fatal Force Database"). Using the comprehensive cross-linked data set, we assessed the proportion of study-identified fatal police shootings that were captured by NVDRS, overall and by state, and by each open-source data set. Results. There were 404 unique study-identified fatal shootings by law enforcement in the 27 states for which data were available from NVDRS, 393 (97%) of which were captured in NVDRS. The proportion of shootings captured by NVDRS varied only slightly by state. Conclusions. The NVDRS provides a comprehensive count of fatal police shootings. Public Health Implications. Expanding NVDRS to all 50 states would provide comprehensive counts of fatal police shootings and detailed circumstantial information about these deaths at the national level. Open-source data can continue to provide real-time data collection as well as more complete information about nonfirearm officer-involved deaths.